TRANSIENT PROCESS AT LOW-ORDER FREQUENCY DEPENDENT DIGITAL COMPONENTS - Ukhina А. V.; Sitnikov, V. S. (Radio Electronics, Computer Science, Control, 2018)
Context. When constructing specialized and programmable mobile systems, there arises the problem of system restructuring, under system functioning conditions breach because of changes in the noise-signaling environment or the system operating conditions. Any rearrangement of the system’s digital frequency-dependent components leads to the occurrence of transient process, which duration is determined by the components characteristics. The traditional approach to the transient process analysis refers to the zero initial conditions, however, the intelligent sensors and specialized computer systems operation as well as parameters adjustment as well as other system components can be performed under non-zero initial conditions. This implies the need for a large number of computations, not feasible sometimes in real time. Here essential is to assess the duration of process’ transition to readjustment process to provide the system operability under new conditions. Objective. To estimate the transient process’ maximum duration when rearrangement, to determine the possible rearrangements range and width, taking into account the system stability. Method. This research carrying out improved is the indirect method of transient process duration estimating by the transfer function poles simplifying the irrational function expansion. Results. The effected analysis with relevant modeling and theoretical verification allowed obtaining relations to estimate the transient process maximum duration and to determine possible modifications range and width taking into account the system stability. Upon research results we built the dependencies of transient process duration onto the cutoff respective frequency. Simplified is the representation of relation used to determine the transient process length at the expense of decomposing into order series. Conclusions. The results obtained allow us to estimate the transient process duration upper limit by improving the indirect method of estimating the transient process duration along the transfer function poles, while simplifying the irrational function expansion, that making possible, before the rearrangement beginning, considering the given new relative cutoff frequency and the component order, to predict the component stability afterwards. From a practical point of view, this reduces the calculations amount and due to the predicted result, increases the specialized computer system overall and by-components efficiency for specified performance criteria. The results obtained are applicable to the design of computer systems’ microprocessor components.